2016
DOI: 10.1093/mutage/gew018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in lncRNAH19are associated with the risk of bladder cancer in a Chinese population

Abstract: The long non-coding RNA (lncRNA) H19 as an imprinted gene transcribed from only the maternal allele has the vital role in carcinogenesis. Aberrant H19 expression is involved in bladder cancer development. In this study, we explored the association between single nucleotide polymorphisms (SNPs) in H19 and bladder cancer risk. Four tagging SNPs (tagSNPs) were selected from the 1000 Genomes Project database. In total, 1049 bladder cancer cases and 1399 controls were recruited in this case-control study. Odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…Our results further revealed the critical in uence of G and A genotype in H19 rs217727. In line with our observations, the study has revealed that the carriers of rs217727 AA genotype had a signi cantly increased risk of bladder cancer in young male patients [59]. Studies demonstrated T variant of rs217727 was strongly associated with an increased risk of coronary artery disease (CAD) and gastric cancer (GC) [60,61].…”
Section: Discussionsupporting
confidence: 86%
“…Our results further revealed the critical in uence of G and A genotype in H19 rs217727. In line with our observations, the study has revealed that the carriers of rs217727 AA genotype had a signi cantly increased risk of bladder cancer in young male patients [59]. Studies demonstrated T variant of rs217727 was strongly associated with an increased risk of coronary artery disease (CAD) and gastric cancer (GC) [60,61].…”
Section: Discussionsupporting
confidence: 86%
“…The rs13252298 and rs1456315 were associated with significantly decreased risks of CRC. Similarly, rs217727 AA in H19 and rs8506G > A in lincRNA‐NR_024015 are associated with increased risk of bladder cancer and non‐cardia gastric cancer, respectively.…”
Section: Lncrna Snps In Cancer Risk Predictionmentioning
confidence: 97%
“…From a functional perspective, lncRNAs are implicated in complex cellular processes via diverse mechanisms including titration of transcription factors, sponging microRNAs (miRNAs) and recruitment of chromatin modifying enzymes . For example, lncRNA‐H19 could interact with methyl‐CpG‐binding domain protein 1 to induce H3K9 methyltransferase to imprinted gene network . Furthermore, lncRNA PVT1 can promote angiogenesis via recruiting STAT3 and STAT3 in turn transactivate PVT1 expression .…”
Section: Introductionmentioning
confidence: 99%